How to Calculate the Exact Angle for Two-level Osteotomy in Ankylosing Spondylitis?. Issue 17 (September 2016) - Zheng, Guoquan; Song, Kai; Yao, Ziming; Zhang, Yonggang; Tang, Xiangyu; Wang, Zheng; Zhang, Xuesong; Mao, Keya; Cui, Geng; Wang, Yan
Abstract : Study Design: A prospective case series study. Objective: To describe and assess a two-level osteotomy method for the management of severe thoracolumbar kyphosis (TLK) in patients with ankylosing spondylitis (AS). Summary of Background Data: To achieve better postoperative outcomes in these patients, a sophisticated preoperative surgical plan is required. Most deformities are managed using a one-level osteotomy and a two-level osteotomy is seldomly reported. Till date, no study has described a two-level osteotomy for these cases. Methods: From January 2011 to December 2012, 10 consecutive patients with ankylosing spondylitis who underwent two-level spinal osteotomy were studied. Pre- and postoperative full-length free-standing radiographs, including the whole spine and pelvis, were available for all patients. Pre- and postoperative radiological parameters, including T5-S1 Cobb angles, TLK, lumbar lordosis, pelvic incidence, pelvic tilt, sacral slope, and sagittal vertical axis were measured. Health related quality of life, including Oswestry Disability Index and Scoliosis Research Society-22 surveys were administered before surgery and at 1-year follow up. Results: The preoperative and postoperative T5-S1 Cobb angles was 51.3° and −7.1°, respectively ( P < 0.001). All patients demonstrated changes in postoperative radiographic parameters including decreased pelvic tilt (from 37.1° to 14.3°, P < 0.001), TLK (from 36.9° to 12.6°, P < 0.001), and sagittal vertical axis (from 21.4 cm to 7.1 cm, P < 0.001), increased lumbar lordosis (from -5.1° to −47.1°, P < 0.001), sacral slope (from 13.4° to 37.7°, P < 0.001), but no significant change in pelvic incidence. Health related quality of life scores at 1-year follow up were significantly improved compared to those before surgery. Conclusion: This calculation of two-level osteotomy provides an accurate and reproducible method for ankylosing spondylitis correction. By which, we can obtain satisfactory radiological parameters and clinical outcomes. Level of Evidence: 4